(untitled) (Third Sector Social Economic Review, 2025)
This study examines the issue of access to clean and affordable energy in the context of the Sustainable Development Goals in Africa. Although Africa is rich in renewable energy resources, much of the continent still lacks access to electricity and clean cooking technologies. This situation is a major obstacle to the continent’s economic development, education, health and social equality. The research examined 337 scientific studies in detail by searching the Web of Science (WoS) and Scopus databases using the keywords ’Africa’ and ’energy’, and analysed them using CiteSpace scientific mapping software. The results show that micro-grids, solar and wind energy, energy financing and regional policy harmonisation are critical. Strengthening international financing mechanisms, increasing public-private partnerships and supporting community-based energy projects are required for a clean energy transformation in Africa. This study provides a theoretical and practical projection of Africa’s energy future, and the recommendations outlined above could accelerate the transition to sustainable energy in Africa. Addressing financing constraints, policy misalignment, and technology adaptation is critical to advancing energy transformation in the region. These literature-based recommendations can help bridge the gap between theoretical research and practical implementation.